Dietary vitamin E on the reproductive performance of the fantail goldfish Carassius auratus auratus - Arfah, Harton; Melati, .; Setiawati, Mia (Jurnal Akuakultur Indonesia, 2013)
ABSTRACT This research was conducted to examine the different dose of vitamin E in the diet on female broodstock reproduction performance of the fantail goldfish Carassius auratus auratus. This research consisted of four treatments with three replications. The use of vitamin E doses was 0, 125, 250, and 375 mg/kg. The vitamin E was dissolved in vegetable oil and mixed with albumen as a binder in feed. The vitamin E was sprayed at feed and was air dried. Female broodstock of the fantail goldfishes were reared for 40 days. The result showed that 375 mg/kg treatment performed the highest quality of reproduction. Egg diameter, gonadosomatic index, fecundity, and germinal vesicle breakdown of fish which are treated by 375 mg/kg vitamin E were respectively 0.92±0.05 mm, 8.86±4.62%, 56.00±29.18%, and 67.35±17.67% higher than control. Thus, 375 mg/kg of dietary vitamin E suplementating was a best dose to improve female broodstock productivity of the fantail goldfish Keywords: female broodstock, fantail goldfish, vitamin E, reproduction quality  ABSTRAK Penelitian dilakukan untuk menguji suplementasi vitamin E dengan dosis berbeda dicampur ke dalam pakan komersial terhadap produktivitas induk betina ikan komet Carassius auratus auratus. Penelitian ini menggunakan empat perlakuan dengan tiga ulangan. Dosis vitamin E yang diberikan, yaitu 0, 125, 250, dan 375 mg/kg pakan. Vitamin E dilarutkan dalam minyak nabati dan dicampur dengan putih telur sebagai perekat pada pakan. Vitamin E disemprotkan ke pakan dan dikeringanginkan. Induk betina ikan komet pascasalin dengan bobot 72,78±19,47 g diberi perlakuan selama 40 hari. Hasil penelitian menunjukkan bahwa induk betina ikan komet yang diberi suplementasi vitamin E sebanyak 375 mg/kg dalam pakan memiliki diameter telur 0,92±0,05 mm, gonadosomatic index 8,86±4,62%, fekunditas 56,00±29,18 butir/g ikan, dan germinal vesicle breakdown 67,35±17,67% yang lebih tinggi dibandingkan kontrol. Dengan demikian, suplementasi vitamin E sebesar 375 mg/kg pada pakan adalah dosis terbaik dalam meningkatkan produktivitas induk betina ikan komet. Kata kunci: induk betina, ikan komet, vitamin E, kualitas reproduksi